2021
DOI: 10.1186/s40900-021-00274-1
|View full text |Cite
|
Sign up to set email alerts
|

Involving older adults in technology research and development discussions through dialogue cafés

Abstract: Background Citizen involvement is important for ensuring the relevance and quality of many research and innovation efforts. Literature shows that inadequate citizen involvement poses an obstacle during the research, development, and implementation of assistive technology. Previous studies have addressed the advantages and disadvantages of citizen engagement in health research and technology development, and there is concern about how to ensure valuable engagement to avoid situations where they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…DTs had an important role in maintaining the social links of OAs, as reported in the literature [ 33 ], and increased their feeling of safety [ 34 ]. DTs were also used to look for information, to enrich general knowledge, or to improve daily life (cooking, DIY), this convenience of DTs being mentioned in the literature [ 35 ]. According to five participants, communicating or searching for information via DTs was important for preserving cognition.…”
Section: Discussionmentioning
confidence: 99%
“…DTs had an important role in maintaining the social links of OAs, as reported in the literature [ 33 ], and increased their feeling of safety [ 34 ]. DTs were also used to look for information, to enrich general knowledge, or to improve daily life (cooking, DIY), this convenience of DTs being mentioned in the literature [ 35 ]. According to five participants, communicating or searching for information via DTs was important for preserving cognition.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study pertains to missing data as not all participants completed each survey or survey question. Engaging older adults in research activities is a known challenge [ 54 ], and participants in our study at times could be overwhelmed by various program activities. Future programs should take this into consideration and keep survey instruments as brief as possible and offer different methods to complete surveys and interviews, for example, on the web, over the phone, or when possible, in person.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple barriers to participatory involvement of older adults in gerotechnology research have been identified, with the majority of the research focusing on barriers stemming from ageism and ableism. More specifically, researchers have identified as barriers the assumptions that older adults are “technology inept and digitally illiterate” [ 13 ] and that their lower use of technologies is due to age-related functional limitations (e.g., vision, hearing, and touch) or their negative attitudes towards such limitations [ 14 ]. This stigma contributes to the limited involvement of older adults in gerotechnology, which in turn reinforces the negative stereotype of older adults as being incapable or uninterested in technology and its development.…”
Section: Introductionmentioning
confidence: 99%